OP0144 Validation of the rabbit risk score for serious infections. (23rd January 2014) - Strangfeld, A.; Manger, B.; Eisterhues, C.; Krause, A.; Listing, J.; Zink, A.
Abstract : Background: Recently we published a score [1] which enables the calculation of the risk of serious infections in individual patients with rheumatoid arthritis (RA) treated either with TNFα inhibitors or conventional DMARDs. Our original analysis was based on patients enrolled in the German biologics register RABBIT between May 2001 and December 2006. Taking changing risks over time (resulting from selection processes and clinical improvement) into account our data provided, for the first time, detailed information about the expected absolute risk of serious infection in individual patients. Objectives: To evaluate these findings in an independent sample of patients not included in the previous analysis. Methods: We used data from patients enrolled in RABBIT after 1st of January 2009 at start of treatment with TNFα inhibitors or conventional DMARDs. Using the RABBIT risk score, we calculated for each patient the expected likelihood of a serious infection based upon the individual risk profile. The expected numbers of serious infections were then compared to the observed numbers in the total cohort and within defined subgroups of patients. Results: Data of 1327 RA patients treated with TNFα inhibitors and of 1276 patients treated with DMARDs were available for the analysis. There was a very good agreement between observed and expected rates of serious infections in the evaluation sample (see table). Of note, the agreement was also high in subgroups of patients with a higher risk of infections. Conclusions: The evaluation of the RABBIT risk score for serious infections in individual patients showed high agreement between observed and expected rates of serious infections in an independent sample of RA patients. The agreement was also high for patients at high risk of infections. The RABBIT risk calculator is therefore useful for rheumatologists to identify patients at increased risk and avoid treatment combinations with a very high risk for serious infections. Acknowledgements: Supported by a joint unconditional grant from Abbott, Amgen/Swedish Orphan Biovitrum, Bristol Myers Squibb, Essex/MSD, Pfizer, Roche, and UCB. References: [1] Strangfeld A, Eveslage M, Schneider M, Bergerhausen HJ, Klopsch T, Zink A, Listing J. Treatment benefit or survival of the fittest: what drives the time-dependent decrease in serious infection rates under TNF inhibition and what does this imply for the individual patient? Ann Rheum Dis 2011; 70(11):1914-20. Disclosure of Interest: None Declared